Phenomenological understanding and electric eels - Gervais, Raoul (THEORIA. An International Journal for Theory, History and Foundations of Science, 2017)
Explanations are supposed to provide us with understanding. It is common to make a distinction between genuine, scientific understanding, and the phenomenological, or 'aha' notion of understanding, where the former is considered epistemically relevant, the latter irrelevant. I argue that there is a variety of phenomenological understanding that does play a positive epistemic role. This phenomenological understanding involves a similarity between bodily sensations that is used as evidence for mechanistic hypotheses. As a case study, I will consider 17th and 18th century research into the mechanism behind the electric eel's power to shock.